Pre-diagnostic leukocyte mitochondrial DNA copy number and colorectal cancer risk. (26th September 2019) - Yang, Keming; Li, Xin; Forman, Michele R; Monahan, Patrick O; Graham, Bret H; Joshi, Amit; Song, Mingyang; Hang, Dong; Ogino, Shuji; Giovannucci, Edward L; De Vivo, Immaculata; Chan, Andrew T; et al.
Abstract: Mitochondrial DNA (mtDNA) is susceptible to oxidative stress and mutation. Few epidemiological studies have assessed the relationship between mtDNA copy number (mtDNAcn) and risk of colorectal cancer (CRC), with inconsistent findings. In this study, we examined the association between pre-diagnostic leukocyte mtDNAcn and CRC risk in a case–control study of 324 female cases and 658 matched controls nested within the Nurses' Health Study (NHS). Relative mtDNAcn in peripheral blood leukocytes was measured by quantitative polymerase chain reaction-based assay. Conditional logistic regression models were applied to estimate odds ratios (ORs) and 95% confidence intervals (95% CIs) for the association of interest. Results showed lower log-mtDNAcn was significantly associated with increased risk of CRC, in a dose-dependent relationship ( P for trend < 0.0001). Compared to the fourth quartile, multivariable-adjusted OR [95% confidence interval (CI)] was 1.10 (0.69, 1.76) for the third quartile, 1.40 (0.89, 2.19) for the second quartile and 2.19 (1.43, 3.35) for the first quartile. In analysis by anatomic subsite of CRC, we found a significant inverse association for proximal colon cancer [lowest versus highest quartile, multivariable-adjusted OR (95% CI) = 3.31 (1.70, 6.45), P for trend = 0.0003]. Additionally, stratified analysis according to the follow-up time since blood collection showed that the inverse association between mtDNAcn and CRC remained significant among individuals with ≥ 5 years' follow-up, and marginally significant among those with ≥ 10 years' follow-up since mtDNAcn testing, suggesting that mtDNAcn may serve as a long-term predictor for risk of CRC. In conclusion, pre-diagnostic leukocyte mtDNAcn was inversely associated with CRC risk. Further basic experimental studies are needed to explore the underlying biological mechanisms linking mtDNAcn to CRC carcinogenesis. Abstract : Pre-diagnostic leukocyte mitochondrial DNA copy number, a reflection of oxidative stress damage, was inversely associated with risk of colorectal cancer, and may be a long-term predictor of colorectal cancer risk.